Mitigation devices in written complaints: A contrastive analysis of native and non-native English speakers - Nur Lailiyah; Monika Widyastuti Surtikanti; Arif Nugroho (Universitas Syiah Kuala, 2026)
Effective communication in written complaints requires the use of appropriate mitigation devices to express dissatisfaction while maintaining politeness. This study aims to examine (1) the differences in the use of mitigation devices in written complaints between native and non-native English speakers, and (2) the factors influencing the choice of these devices. The study employed a qualitative content analysis design, using 100 complaint texts collected from Twitter and TripAdvisor, consisting of 50 texts from native speakers and 50 from non-native speakers. Data were analyzed using a coding framework covering hedging, indirect language, politeness markers, and expressions of empathy or acknowledgment, supported by a contextual analysis of the influencing factors. The findings reveal that native speakers employ a wider range and combination of mitigation devices, whereas non-native speakers tend to use more direct and less varied expressions of dissatisfaction. In addition, the study identifies pragmatic competence, cultural background, and communication platform as key factors influencing mitigation choice. Native speakers consistently demonstrate more varied and combined use of mitigation strategies across contexts, while non-native speakers show more limited use, particularly in informal platforms, such as social media. These findings suggest the importance of explicit instruction in pragmatic competence to improve non-native speakers’ ability to use mitigation devices effectively. The study also provides practical implications for language teaching and cross-cultural communication, particularly in enhancing written complaint strategies in digital contexts.